2006
DOI: 10.3758/bf03193421
|View full text |Cite
|
Sign up to set email alerts
|

Size congruity effects with two-digit numbers: Expanding the number line?

Abstract: Is 7 greater than 5? This appealingly simple question prompts a rapid and accurate answer with virtually all people. The ease with which people respond conceals the fact that complex cognitive operations are involved. To respond, people must retrieve the underlying magnitudes; note that, as mere graphic signs, 7 is neither larger nor smaller than 5. This fast (automatic?) retrieval of numerical information is particularly impressive when numerical values are irrelevant to the task at hand and can actually hurt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
78
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 47 publications
8
78
0
1
Order By: Relevance
“…Therefore, the U-T presentation should facilitate the relevant decades comparison, whereas the T-U presentation should involve a greater interference of the units comparison. However, if the type of processing of two-digit numbers essentially depends on the mode of presentation (simultaneous 0parallel processing vs. sequential 0 holistic processing), as it has also been suggested recently (Ganor-Stern et al, 2009;Zhang & Wang, 2005;Zhou et al, 2008; but see Moeller et al, 2009), then a holistic comparison process should be found in our three conditions. Indeed, our three conditions corresponded to a sequential presentation, as in all of them the target numbers had to be compared to the standard 55 kept in memory.…”
Section: Numerical Comparison Of Two-digit Numbersmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the U-T presentation should facilitate the relevant decades comparison, whereas the T-U presentation should involve a greater interference of the units comparison. However, if the type of processing of two-digit numbers essentially depends on the mode of presentation (simultaneous 0parallel processing vs. sequential 0 holistic processing), as it has also been suggested recently (Ganor-Stern et al, 2009;Zhang & Wang, 2005;Zhou et al, 2008; but see Moeller et al, 2009), then a holistic comparison process should be found in our three conditions. Indeed, our three conditions corresponded to a sequential presentation, as in all of them the target numbers had to be compared to the standard 55 kept in memory.…”
Section: Numerical Comparison Of Two-digit Numbersmentioning
confidence: 99%
“…Since Nuerk et al's (2001) study, the compatibility effect has been largely replicated: with German verbal written numerals (Nuerk, Weger, & Willmes, 2002; with Arabic numerals presented in diagonal (Nuerk, Weger, & Willmes, 2004), as well as horizontally (Ganor-Stern, Tzelgov, & Ellenbogen, 2007); with Arabic numerals in native German speakers whose number word system presents an inversion property (e.g., 22: ''zweiundzwanzig'' 0''two-and-twenty''), but also in native English (Nuerk et al, 2005) and Spanish (Macizo & Herrera, 2008) speakers whose number word system does not present an inversion property (e.g., 22: ''twenty-two'' in English, ''veintidó s'' in Spanish); and in schoolaged children (Mussolin & Noë l, 2008). Moreover, recent neuroimaging studies found neural correlates of the compatibility effect in the intraparietal cortex (Wood et al, 2008;Wood, Nuerk, & Willmes, 2006).…”
mentioning
confidence: 99%
See 3 more Smart Citations